The influence of teacher performance and motivation on the management of sports education learning set - Aditya Tito Aji Darmawan; Mansur Mansur (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2019)
Management of learning devices is an important factor supporting the success of physical education teachers in teaching, many previous studies have revealed this but there are still many limitations, especially in the discussion of teacher motivation and performance has an influence on the management of learning tools. The purpose of this study was to determine the effect of performance and motivation of physical education teachers on the management of learning devices. This type of research is descriptive quantitative research, using survey methods. Data collection techniques in this study used questionnaires. The population in this study were sports and health physical education teachers at State and Private Vocational Schools in Sleman Regency. The study sample was 66 teachers. The research data analysis technique uses quantitative descriptive analysis with percentages. The results showed that F shows F count of 40.307 greater than F table at a significance level of 5% of 3.1428 (40.3073.1428), this indicates that teacher performance (X1) and teacher motivation (X2) are jointly the same contributes significantly to the learning device management variable (Y).